Risk factors and outcome of Acinetobacter infection in the intensive care unit of a tertiary center in Oyo State, Nigeria (2013)
Acinetobacter plays an important role in the infection of patients admitted to hospitals. Acinetobacter are free living gram-negative coccobacilli that emerge as significant nosocomial pathogens in the hospital setting and are responsible for intermittent outbreaks in the intensive care unit. The aim of this study was to determine the risk factors and outcome of Acinetobacter infections in patients admitted into the intensive care unit of a tertiary center in Oyo State, Nigeria. A total of one hundred patients were recruited for the study, catheter specimen urine, tracheal aspirate and blood culture were collected aseptically from the patients. The specimens were cultured on blood and MacConkey and the organisms identified using Microbact 12E (0xoid). Fourteen (14%) of the 100 patients recruited into the study developed Acinetobacter infection. Chronic obstructive pulmonary disease, endotracheal intubation, and duration of endotracheal intubation were associated risk factors with only duration of endotracheal intubation specifically an 8 to 14 day period being an independent risk factor for Acinetobacter. Six of the patients died of the infection while the remaining eight were discharged from the ICU. The findings that chronic obstructive pulmonary disease and duration of endotracheal intubation being associated with Acinetobacter infection and the attendant mortality associated with the infection should draw attention to this seemingly silent epidemic in our Intensive Care Units so that effective surveillance protocols can be deployed to manage this infection whenever it rears its head.